Hubungan Pelayanan Prima terhadap Kepuasan Pasien di Instalasi Rawat Inap Depati Payung RSU Mayjen H.A Thalib Sungai Penuh Tahun 2024 - Friandi, Riris; Emitrafariona, Emitrafariona; Putri, Dian Eka (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2024)
Based on Eurostat Statistics Explained in 2021, France recorded the highest discharge rate for all inpatients (41,100 per 100,000 population for inpatients) among EU member countries. Excellent service is oriented towards patient satisfaction, so health workers must provide optimal service. Excellent service in primary health care aims to provide satisfaction to the public for public services. Trust being formed among the community certainly provides benefits for primary health services. This research aims to determine the relationship between excellent service and patient satisfaction. This type of research is quantitative and analytical with a cross-sectional study approach. The sampling technique used in this research was the random sampling technique. The population in this study was all 228 patients treated at the Depati Payung Inpatient Installation in 2024 from January to February with a sample of 70 respondents. The results showed that more than half of the 38 (54.3%) respondents with excellent service were not good, and more than half of the 37 (52.9%) respondents with patient satisfaction were less satisfied with the results of the statistical test (Chi-Square) obtained by a p-value of 0.034. The research conclusion shows a relationship between excellent service and patient satisfaction. The researchers' suggestions from the research results can be applied in daily nursing practice, such as providing excellent service so that patients will be satisfied with the services provided by nurses.